US workforce gaps in emergency management: A mixed-methods approach of demographics, capacity, and community engagement - Ananya Verma; Lorraine A. Schneider; Rita V. Burke (PLoS ONE, 2026)
Introduction Within emergency management, few studies have analyzed the shifting landscape of the workforce in the United States. As emergency management is an evolving field, it is important to note changes in the profession. The purpose of this study was to examine the current emergency management workforce, specifically analyzing its demographic breakdowns, organizational concerns, and community-based dynamics. The intent was to determine if the workforce is representative of the communities they work in. Disasters are known to disproportionately impact vulnerable populations, making it more important for emergency managers to be demographically and functionally diverse to effectively reach and prepare these communities. Methods Using a mixed-methods approach, data were gathered through five focus group sessions, and using themes from the focus groups, a large-scale survey was designed and disseminated to seven emergency management organizations across the country. The survey collected responses for three weeks, and participants were offered the opportunity to enter a raffle for a $100 gift card. The focus group data were analyzed using Atlas.ti, and the survey data were analyzed using Microsoft Excel. Results In total, 20 emergency managers participated in the focus groups, and 232 participants completed the survey. Our analysis showed high levels of concern regarding an overall lack of funding and resources within organizations. Other concerns included insufficient representation of historically underrepresented populations, limiting emergency managers’ capacity to effectively engage their communities. Conclusions This study identifies key challenges within the evolving emergency management workforce, most notably limited funding, the risk of burnout, underrepresentation of minority groups in leadership, and lack of standardization. At the same time, encouraging trends are emerging, including greater gender diversity and growing participation from younger professionals. The findings provide a foundational overview to guide future research on strengthening and supporting the workforce and the communities they serve.